Paramedics' perspectives of the community paramedic role in Ontario. (2nd February 2023) - Agarwal, Gina; Pirrie, Melissa; Angeles, Ricardo; Marzanek, Francine; Keenan, Amelia; McLeod, Brent; Cockerell, Krista; Reed, Buck
Abstract : Background: Community paramedicine (CP) expands the paramedic role to emergency call prevention, yet little research has examined paramedics' perspectives of CP. Aims: This study sought to explore paramedics' views regarding the CP role and training. Methods: A cross-sectional, web-based survey of Ontario paramedics measured perceptions, support and interest in CP. Descriptive and regression analyses were conducted. Findings: Of the 452 participants, 57.5% were male, 43.6% primary care paramedics and 33.0% had a history of being on modified duty. Paramedics perceived CP to include treat-and-release (85.4%), community resource referrals (79.0%), expanded skills (77.9%), community education (75.9%) and follow-up (73.7%). Most were supportive (82.8%) and interested in participating (72.3%). Interest in training was lower in respondents with 20 or more years of service and higher in those with a history of modified duty ( p <0.05). Conclusion: Paramedics are aware the CP role has multiple functions and are supportive and interested in CP. This study has implications for services as CP expands globally.